Hematological Parameters, Lipid Profile, and Cardiovascular Risk Analysis Among Genotype-Controlled Indigenous Kiwcha Men and Women Living at Low and High Altitudes - Ortiz-Prado, Esteban; Portilla, David; Mosquera-Moscoso, Johanna; Simbaña-Rivera, Katherine; Duta, Diego; Ochoa, Israel; Burgos, German; Izquierdo-Condoy, Juan S.; Vásconez, Eduardo; Calvopiña, Manuel; Viscor, Ginés (Frontiers in Physiology, 2021)
Introduction: Human adaptation to high-altitude is due to characteristic adjustments at every physiological level. Differences in lipid profile and cardiovascular risk factors in altitude dwellers have been previously explored, nevertheless there are no reports available on genotype-controlled matches among different altitude adapted indigenous populations. Objective: To explore the possible differences in plasma lipid profile and cardiovascular risk among autochthonous Kiwcha people inhabitants of low and high-altitude locations. Methodology: A cross-sectional analysis of plasmatic lipid profiles and cardiovascular risk factors in lowland Kiwchas from Limoncocha (230 m) and high-altitude Kiwchas from Oyacachi (3,800 m). Results: In the low altitude group, 66% were women (n=78) and 34% (n=40) were men, while at high altitude, 59% (n=56) were women and 41% (n=41%) were men. We found the proportion of overweight and obese individuals to be higher among low altitude dwellers (p<0.05). Red blood cells (RBC), Hemoglobin concentration and SpO2% were higher among high altitude dwellers and erythrocyte’s size was found to be smaller at high altitude .The group located at low altitude showed also lower levels of plasma cholesterol, LDL and HDL but most of these differences are not influenced by gender or elevation. Conclusions: Living at altitude elicits well-known adaptive physiological changes such as erythrocyte count, hemoglobin concentration, hematocrit, and serum glucose. We report also clinical differences in the plasma lipid profile, with higher levels of cholesterol and high density and low-density lipoproteins in Andes Mountain inhabitants versus their Amazonian basin peers. Despite we found altered underlying physiological pathways between the populations, this does not allow in a different cardiovascular risk.